ANALISIS PENDAPATAN DAN PERSEPSI PETANI TERHADAP KEMITRAAN USAHA KAMPUNG KUCAI DI KABUPATEN BLITAR - Brillian Pintakami, Lintar; Wahyu Budiman, Eko (Universitas Islam Balitar, 2021)
This study aims to describe the agribusiness partnership process that takes place in Kampung Kucai, analyze the income of chives farming, and the perception of chives farmers on the partnership process in Garum District, Blitar Regency. This research uses a qualitative approach in the form of a case study. Informants in this study were partner chives farmers in Kampung Kucai. Determination of the sample of plasma partner farmers was carried out by purposive sampling method. Informants were selected based on secondary data from the core and information from farmers. So the sample used for Kucai Mitra farmers is 20 people. In addition, there are also 5 key informants. The methods of data collection carried out in this study are of several types, namely structured interviews, in-depth interviews, participatory observations, and documentation. The data analysis method used in this researchis descriptive analysis, income analysis, and Likert analysis. The results showed that the type of partnership between the Financial Institution